The influence of concept mapping on achievement, self-regulation, and self-efficacy in students of English as a second language. - Chularut, Pasana. (My University, 2001)
This study investigated the effectiveness of concept mapping used as a learning strategy with students in English as a Second Language classrooms. Seventy-nine ESL students participated in the study. Variables of interest in the study were (a) students' achievement when learning from text, (b) students' reports of use of self-regulation strategies (self-monitoring and knowledge acquisition strategies), and (c) students' self-efficacy for learning from text in English. A randomized pretest-posttest control group design with (a) concept mapping group and (b) an alternative learning strategy group was employed. A Split-Plot Analysis of Variance and a Split-Plot Multivariate Analysis of Variance were computed. The findings showed the statistically significant interaction of time and method of instruction for achievement, self-monitoring, knowledge acquisition strategies, and self-efficacy. For all variables, the concept mapping group showed significantly greater gains from pre-test to post-test than the alternative learning strategy group. These findings support the predictions that students in the concept mapping condition would outperform students in the alternative learning strategy condition on achievement, self-monitoring, knowledge acquisition strategies, and self-efficacy. The findings have implications for both practice and research.
Keywords: Education, Educational Psychology.; English language Study and teaching Foreign speakers.; Education, Language and Literature.; Concept learning.